The Influence of Organizational Culture and Work Discipline on Teacher’s Professionalism - Karnela, Rita; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2022)
This study examined the organizational culture and work discipline on teacher’s professionalism. This study belongs to qualitative method. The data were collected using questionnaire and documentation. The results showed organizational culture and work discipline significantly influences the professionalism of SMA Negeri 1 Belimbing teachers both partially and simultaneously. This study reveals the principals to more pay attention the organizational culture and work discipline where they will gain teacher’s professionalism.